Kontribusi Hasil Belajar Mata Kuliah Kewirausahaan Dengan Minat Berwirausaha Di Bidang Florist Pada Mahasiswa Pendidikan Tata Rias Universitas Negeri Jakarta - Silvia Fertyasari; Lilies Yuastri; Lilis Jubaedah (Universitas Negeri Jakarta, 2023)
This research is motivated by makeup education students' lack of interest in opening a florist business. This study aims to determine the extent to which the learning outcomes of entrepreneurship courses contribute to the interest in entrepreneurship in the field of floristry among makeup education students. This type of research is descriptive research with a correlational approach, involving a population of 36 makeup education students from the class of 2018 at Jakarta State University. The sampling technique in this study used total population sampling. The data used are primary and secondary data. This research instrument is a questionnaire using a Likert scale consisting of 5 answer choices. Analysis requirements test. The analysis requirements test in this study uses the Kolmogorov-Smirnov test, which shows a probability value (sig) of 0.070 > 0.05, indicating a significant level. Therefore, both variables can be considered normally distributed, and the linearity value shows a significant deviation from linearity, with a value of 0.800 > 0.05. Hypothesis testing using a simple linear regression test shows that the calculated r significantly deviates from the linearity value of 0.215, indicating it is less than the table r of 0.3291. This suggests that Ha is rejected and Ho is accepted. The correlation value is 0.215, and the magnitude of the influence of the dependent variable is 0.046. It is concluded that the contribution of the independent variable to the dependent variable is 4.6%, while the rest is influenced by other variables.